Development of the 1000 Gardens Community Program in the City of Bandung - Tine Ratna Poerwantika; Shylvia Windary; Mochamad Ichsan Kamil; Khanza Azhari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The 1000 Gardens Community was established in 2015, where they used idle land for farming. There are three main problems faced by the community, namely: difficulties in inviting the community to participate in the program, difficulties in providing facilities and infrastructure for building communal shelters, and a lack of expertise in running business and marketing. The results of program assistance have succeeded in increasing interest in community participation as indicated by an increase in the number of program participants. Assistance in procuring raw materials and training on business and marketing strategies has succeeded in providing a new perspective for community administrators to run Community-owned business units.